IMPLEMENTASI KEBIJAKAN PROGRAM DESA TANGGUH BENCANA (DESTANA) DI BIDANG PENCEGAHAN DAN KESIAPSIAGAAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN SUMEDANG - Suherman; Nugraha, Agan; Nugraha, Hendra Ali; Karlina, Neneng Rita; Sa'adah, Nurholis; Sari, Wulan (JRPA - Journal of Regional Public Administration, 2025)
This research aims to determine, obtain objective data and information about the implementation of the Disaster Resilient Village (DESTANA) program policy in the field of prevention and preparedness of the Regional Disaster Management Agency (BPBD) of Sumedang Regency. In this study, researchers used descriptive qualitative research methods. The data collection techniques used were literature study, observation, interviews, and documentation. The technique of determining informants using purposive sampling with the number of research informants as many as 4 people, namely the Secretary of the Agency, the Head of the Prevention and Preparedness Section, and 2 Prevention and Preparedness Section Staff. The results showed that the implementation of the Disaster Resilient Village (DESTANA) program policy in the Prevention and Preparedness Section of the Sumedang Regency Regional Disaster Management Agency (BPBD) has not fully run optimally. This can be seen from several factors that hinder the implementation of program policies so that they do not run optimally, such as human resources that are still less competent, inadequate facilities and infrastructure, budget costs that are still insufficient, and communities that lack knowledge, understanding, and awareness of disaster hazards. Thus, it is very necessary to make efforts to minimize the obstacles that have occurred, such as improving the quality of human resources by conducting training and training.